1028 Early response to a low- dose acubitril/valsartan (ARNI) therapy among stable symptomatic patients with HFrEF. (17th January 2020) - Sacharczuk, W; Dankowski, R; Baszko, A; Sowinska, A; Ozegowski, S; Szyszka, A
Abstract: Funding Acknowledgements: no financial support Background: Sacubitril/valsartan (S/V) has shown to improve outcomes, that is related to reverse remodeling of the left ventricle (LV) with improved ejection fraction (LVEF) and mitral regurgitation (MR) during long-term therapy. There are limited data on early effects of S/V treatment with respect to the left ventricle function and echocardiographic evaluation of this phenomenon. Aim of the study was to evaluate the early effect of a starting-dose of S/V administered in patients (pts) with stable symptoms of heart failure on clinical symptoms, laboratory tests and echocardiographic parameters using global longitudinal strain (GLS) as a sensitive parameter detecting improvement of LV function. Methods: Twenty pts (mean age 60 years, 2 female), with HFrEF (NYHA class II-III) on optimal medical treatment with ICM (75%) or NICM (35%) were included to low-dose S/V treatment (24/26mg) after excluding contraindications. Clinical and echocardiographic evaluation was performed at baseline and after 30 days. The following parameters have been measured: 6-Minutes Walking Test (6MWT) and Minnesota Living with Heart Failure questionnaire, laboratory results and echocardiographic assessment with speckle tracking technique (STE). Results: All pts completed 30 days treatment period without complications and no change to medication. During this period the mean values of RR decreased significantly (SBP 129, 4mmHg vs 121, 25mmHg and DBP 81, 6mmHg vs 79, 2mmHg respectively). Other clinical parameters did not change. There were no differences NT-pro BNP and TNT levels (respectively 1726 vs 1930 pg/ml and 26 vs 22 ng/ml). After 30days, the mean 6MWT distance increased by 50m (349, 5 vs 401, 5m p < 0.01), and a positive response was observed in Minnesota Living with Heart Failure Questionnaire (p < 0.001). Echocardiographic parameters revealed positive remodeling of LV and left atrium (LA). There was a significant improvement in LVEDd (67, 9mm vs 64, 9mm, p < 0.01), LVESd (61, 6mm vs 58, 8mm, p < 0.01) and stroke volume (40, 5 to 45, 8ml, p < 0.01). There was no significant increase in LVEF (30% vs 31, 5%, p = 0.052). The diastolic parameters of LV function didn't change during the study. The LA volumes significantly decreased (110 vs 92ml, p < 0.01) during the treatment period as well as the degree of MR (ERO 0.51 vs 0, 37 p < 0.01). Out of several LV deformation parameters, only global longitudinal strain has changed significantly (GLS-6, 1% vs -7, 0%, p = 0, 02). The improvement in symptoms and 6MWT correlated only with global systolic radial (RS) and longitudinal (GLS) strain correlated positively after 30 days treatment. Conclusion:Thirty days treatment with low-dose S/V in stable, symptomatic HFrEF patients leads to symptomatic and clinical improvement which correlates with positive remodeling of the left ventricle and reduces the degree of mitral regurgitation. The GLS is a sensitive indicator of LV function improvement after short time S/V treatment and may be used to assess early response.